Virtual ( Electronic ) Reference Services In Academic Libraries: Virtual ( Electronic ) Reference Services In Academic Libraries (Journal of the College of Education for Women, 2019)
AbstractThis paper deals with the concept of electronic reference services in academiclibraries , showing forms of communications , training needs for reference librariansand the role of the librarian in the new technological environment.